Four C’s Skills Integration in the Lesson Plans of Grade 7 English Teacher - Tamela, Ellis; Dwi, Maura Hanifah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
Four C skills’ integration in English curriculum has been investigated in recent years. Unfortunately, those studies focused on the integration of 4Cs in lesson plans carried out in elementary schools. Thus, this research aimed to analyze how the 4C skills were implemented in English lesson plans of 7th grade. The data were collected through content analysis on ten lesson plans of public and private junior high schools in Jakarta and Bekasi. It was found that all analyzed lesson plans have incorporated the 4Cs skills; communication, collaboration, critical thinking, and creativity. However, there were indicators of each skill that more dominantly appeared in a certain topic or were seen not to be incorporated in any examined lesson plans. In addition, teachers mostly incorporated the 4Cs skills in the learning activity and assessment. Although all the analyzed lesson plans have integrated 4Cs, the fulfilment of the indicators of each skill still needed to be improved. These findings are expected to be a recommendation for educators especially English teachers in designing lesson plans which integrated the 4C skills as the keys to a lifetime of learning and creative work as the current world of work is required leads to the need for integration of 4Cs in the classroom.